2014
DOI: 10.1111/jcmm.12471
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of sunitinib resistant renal cell carcinoma cells after sequential treatment with RAD001 (everolimus) or sorafenib

Abstract: Sequential application of target drugs is standard procedure after renal cell carcinoma (RCC) patients develop resistance. To optimize the sequence, antitumour effects of the mTOR inhibitor RAD001 or the tyrosine kinase inhibitor (TKI) sorafenib on RCC cells with acquired resistance to the TKI sunitinib was evaluated. RCC cells were exposed to 1 μM sunitinib for 24 hrs (as control) and for 8 weeks (to induce resistance) and then switched to RAD001 (5 nM) or sorafenib (5 μM) for a further 8 weeks. Tumour cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
1
28
1
Order By: Relevance
“…In terms of the RCC cell targeted activity of TKIs, it was shown that the short-term (24 h) application of sunitinib in renal cell carcinoma Caki-1 and KTC-26 cell lines induced cell growth inhibition, which was halted in the M and G 2 phases. The signs of anti-RCC cell toxicity became apparent when the cells were exposed to 10 µM of sunitinib; additionally, sorafenib caused a distinct downregulation of the tumor cell number at a dosage of ≥5 µM (63). However, when RCC cells were exposed to 1 µM sunitinib for 8 weeks (equivalent to a 1.3 treatment cycle) cdk1 and cdk2 were overexpressed, p27 was downregulated, and Akt, Rictor, and Raptor were activated (63).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the RCC cell targeted activity of TKIs, it was shown that the short-term (24 h) application of sunitinib in renal cell carcinoma Caki-1 and KTC-26 cell lines induced cell growth inhibition, which was halted in the M and G 2 phases. The signs of anti-RCC cell toxicity became apparent when the cells were exposed to 10 µM of sunitinib; additionally, sorafenib caused a distinct downregulation of the tumor cell number at a dosage of ≥5 µM (63). However, when RCC cells were exposed to 1 µM sunitinib for 8 weeks (equivalent to a 1.3 treatment cycle) cdk1 and cdk2 were overexpressed, p27 was downregulated, and Akt, Rictor, and Raptor were activated (63).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Juengel et al [130] reported that everolimus resistance in vitro was characterized by elevated expression of Akt and S6K1, as well as cell-cycle-activating proteins CDK2 and cyclin A, which allowed for the subsequent increased number of G 2 /M-phase cells. In a follow-up study, they reported that everolimus evoked a strong response in sunitinib-resistant RCC cells by inducing cell growth delay in G 0 /G 1 and diminishing expression levels of p-Akt, p-raptor and p-rictor [131]. Everolimus also counteracted chronic sunitinib-induced CDK1 and CDK2 upregulation.…”
Section: Cellular Effects Of Everolimusmentioning
confidence: 95%
“…One strategy to overcome these limitations has been to test combinations of rapalogues with other known inhibitory agents. For example, both Juengel et al [131] and Larkin et al [132] demonstrated the potential of using everolimus as a second-line therapy following failure of first-line sunitinib treatment. Yao et al [206] showed improved efficacy of everolimus and octreotide combination to treat neuroendocrine tumours compared with everolimus alone.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…In light of the fact that renal carcinoma is one of the most deadly types of cancers, some candidates have been introduced to stop and/or limit the progression of the metastasis of this carcinoma, for example, sunitinib and pazopanib, drugs that are reported to be the inhibitors of tyrosine kinase (6,7). Indeed, these agents were found to be able to stop the growth of cancer cells but extensive research on these agents revealed that they are associated with drug resistance and they have various side-effects as well (8,9). Therefore, there is a need to introduce potent candidates that are originated from a natural source and are not destructive to the normal physiological condition of cells or tissue.…”
Section: Introductionmentioning
confidence: 99%